Factors that influence employees work performance / Fatihah Norazami Abdullah - Abdullah, Fatihah Norazami (2014)
Organization can measure the successful of work procedures by look their work performance level of employs. Good employee's performance can give big impact on company. Therefore, employer responsible to ensure their employees work performance was performed well. Hence, this research is to examine factors that influence employees work perfom1ance. This research was assesses with four factors, which are financial reward, , workplace environment, training, and supervisor support. Moreover, the objective of this research are to know what are the factors that influence employees work performance and to identify the main factors that influence employees work performance, In addition, 30 of respondents on administration of student affair division at UiTM Puncak Alam Selangor were selected to answer the questionnaires. Data from questionnaires feedback was managed by using Statistical Package for Social Sciences (SPSS). Data and results were presented by using frequency analysis, descriptive analysis, and reliability analysis. Furthermore, after conducting this research, the finding was indicated that financial reward, workplace environment, training, and supervisor support was influence employees work performance while, main factor that influence work performance is workplace environment. Some recommendations have been proposed at the end of this research.